2019
DOI: 10.1186/s12917-019-2145-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a model for equine small intestinal disease: effects of extracorporeal blood perfusion of equine ileum on metabolic variables and histological morphology – an experimental ex vivo study

Abstract: BackgroundIn horses a number of small intestinal diseases is potentially life threatening. Among them are Equine Grass Sickness (EGS), which is characterised by enteric neurodegeneration of unknown aetiology, as well as reperfusion injury of ischaemic intestine (I/R), and post-operative ileus (POI), common after colic surgery. The perfusion of isolated organs is successfully used to minimize animal testing for the study of pathophysiology in other scenarios. However, extracorporeal perfusion of equine ileum so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies have explored intestinal segment perfusion to develop in vivo-like preclinical models for research in gastroenterology and intestinal transplantation 120,121 (Table 3). Unterköfler et al 120 developed an NMP platform to perfuse ilea from DCD horses for 4 h, which employed a solution based on autologous blood and plasma perfused through the aboral artery and recirculated through cannulated aboral and oral veins. The authors confirmed intestinal viability via general NMP analyses and ileal motility; however, they noted increased organ weight and lactate levels.…”
Section: Promising Nmp Systems In Other Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have explored intestinal segment perfusion to develop in vivo-like preclinical models for research in gastroenterology and intestinal transplantation 120,121 (Table 3). Unterköfler et al 120 developed an NMP platform to perfuse ilea from DCD horses for 4 h, which employed a solution based on autologous blood and plasma perfused through the aboral artery and recirculated through cannulated aboral and oral veins. The authors confirmed intestinal viability via general NMP analyses and ileal motility; however, they noted increased organ weight and lactate levels.…”
Section: Promising Nmp Systems In Other Organsmentioning
confidence: 99%
“…The administration of therapies through the perfusate has several benefits that make NMP an attractive therapeutic option, including more efficient delivery, lower doses, and reduced unwanted side effects in nontarget organs. 174 The immunomodulatory properties of mesenchymal stem cells 57–159 and multipotent adult progenitor cells 160–162 have shown beneficial effects during liver, lung, and kidney NMP, presumably due to their immunomodulatory properties, which prompt both anti-inflammatory and regenerative responses. 157,160–162 In human models, initially discarded kidneys 160 and livers 161 treated with multipotent adult progenitor cells or preterm-neonate progenitor cells 162 exhibited improved viability, even meeting established criteria.…”
Section: Remaining Challenges and The Future Of Nmp Systemsmentioning
confidence: 99%